The 5XFAD Mouse Model of Alzheimer's Disease Exhibits an Age-Dependent Increase in Anti-Ceramide IgG and Exogenous Administration of Ceramide Further Increases Anti-Ceramide Titers and Amyloid Plaque Burden - Dinkins, Michael B. (J Alzheimers Dis, 2015)
We present evidence that 5XFAD Alzheimer's disease model mice develop an age-dependent increase in antibodies against ceramide, suggesting involvement of autoimmunity against ceramide in Alzheimer's disease pathology. To test this, we increased serum anti-ceramide IgG (2-fold) by ceramide administration and analyzed amyloid plaque formation in 5XFAD mice. There were no differences in soluble or total amyloid-β levels. However, females receiving ceramide had increased plaque burden (number, area, and size) compared to controls. Ceramide-treated mice showed an increase of serum exosomes (up to 3-fold using Alix as marker), suggesting that systemic anti-ceramide IgG and exosome levels are correlated with enhanced plaque formation.